2022
DOI: 10.2319/043021-342.1
|View full text |Cite
|
Sign up to set email alerts
|

Association between malocclusion and articulation of phonemes in early childhood

Abstract: Objectives To evaluate the relationship between dental malocclusion and speech to understand the etiology of speech sound disorders (SSD) in schoolchildren and to make a correct diagnosis and treatment plan. Materials and Methods Articulation and dental occlusion, oromyofunctional evaluation with orofacial praxis and musculature, resting tongue position, and swallowing pattern were analyzed in 290 schoolchildren between the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
5
0
4
Order By: Relevance
“…Several studies noted that patients with AOB show increased rates of sound production errors, with interdental lisping as a common visual and auditory distortion [19][20][21]. Common SSDs in the AOB population also include sibilants such as [s] and [z] as well as postalveolar affricate [tS] (<ch>) and labiodental fricatives [f] and [v] [73,74]. Keyser et al found a 10-fold increased prevalence of interdental and auditory distortions compared with controls for sequences including /ta/, /la/, /sa/, /si/, and /sIsi/ [19,66].…”
Section: Vertical Discrepancies: Anterior Open Bitementioning
confidence: 99%
“…Several studies noted that patients with AOB show increased rates of sound production errors, with interdental lisping as a common visual and auditory distortion [19][20][21]. Common SSDs in the AOB population also include sibilants such as [s] and [z] as well as postalveolar affricate [tS] (<ch>) and labiodental fricatives [f] and [v] [73,74]. Keyser et al found a 10-fold increased prevalence of interdental and auditory distortions compared with controls for sequences including /ta/, /la/, /sa/, /si/, and /sIsi/ [19,66].…”
Section: Vertical Discrepancies: Anterior Open Bitementioning
confidence: 99%
“…Severe malocclusion can lead to both physiological and psychological effects, including impairments in chewing function, speech articulation, and aesthetic appearance. This can have a lasting negative impact on self-esteem and social interactions over time [3].…”
Section: Introductionmentioning
confidence: 99%
“…Так, вираженість мезіального, відкритого та глибокого прикусів, діастеми, збільшення сагітального перекриття, асиметрії мають високу тенденцію асоціюватися з розладами мовлення. Низьку тенденцію мають протрузія верхніх різців, дистальний та перехресний прикуси [4]. Спотворення мови спостерігаються у 18 разів частіше у пацієнтів із мезіальним прикусом порівняно з контрольною групою без патології [5].…”
Section: Introduction / вступunclassified